2013
DOI: 10.1037/a0030915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the Conners’ Continuous Performance Test-II to detect poor effort in U.S. Military personnel following traumatic brain injury.

Abstract: The purpose of this study is to examine the clinical utility of the Conners' Continuous Performance Test (CPT-II) as an embedded marker of poor effort in military personnel undergoing neuropsychological evaluations following traumatic brain injury. Participants were 158 U.S. military service members divided into 3 groups on the basis of brain injury severity and performance (pass/fail) on 2 symptom validity tests: Mild Traumatic Brain Injury (MTBI)-Pass (n = 87), MTBI-Fail (n = 42), and severe traumatic brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…In current study, dependent variables included errors of Omission (sustained attention), Commission (inhibitory control), motor response Variability, and the d’ signal detection parameter (detectability). These variables of the CPT-II have been commonly used in many previous studies (Busse and Whiteside, 2012; Fasmer et al, 2016; Hervey et al, 2006; Hurks et al, 2005; Lange et al, 2013; Lucke et al, 2015). Raw scores were used instead of norm-referenced scores because we planned to include age and sex into all study analyses to statistically account for variance related to these factors.…”
Section: Methodsmentioning
confidence: 99%
“…In current study, dependent variables included errors of Omission (sustained attention), Commission (inhibitory control), motor response Variability, and the d’ signal detection parameter (detectability). These variables of the CPT-II have been commonly used in many previous studies (Busse and Whiteside, 2012; Fasmer et al, 2016; Hervey et al, 2006; Hurks et al, 2005; Lange et al, 2013; Lucke et al, 2015). Raw scores were used instead of norm-referenced scores because we planned to include age and sex into all study analyses to statistically account for variance related to these factors.…”
Section: Methodsmentioning
confidence: 99%
“…Upon application of the criteria proposed by Lange et al (2013), 53 participants (88%) were found to provide consistent effort (good effort group: GEG) while seven participants (12%) were identified as providing poor effort (poor effort group: PEG) at baseline. Number of perseverative errors was the most sensitive indicator for identifying the PEG (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the cutoffs for identifying “poor effort” from the CPT‐2 measures, as well most all other embedded and formal effort measures, strongly favor specificity over sensitivity. In the mTBI study from which are cutoffs were derived, sensitivity was 0.41 with specificity of 1.00; in other words, while only 41% of those who gave poor effort were identified with these cutoffs, there were no “false positives” cases (Lange et al , ). In an RCT, placing greater weight on sensitivity over specificity gives individual participants the benefit of uncertainty, and allows investigators to retain more data points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slightly different pattern with the same take‐home message has been observed on a common measure of sustained visual attention. This measure was sensitive to the effects of effort only; that is, for both civilian and military populations with obvious secondary gain incentives, poor effort significantly diminished performance, but TBI severity did not (Lange et al, ; Ord et al, ).…”
Section: Prospective Methods To Examine Response Validitymentioning
confidence: 99%